NEGATIVE BI IN ROMANI . INDIC AND IRANIAN CONNECTIONS (Bucharest Working Papers in Linguistics, 2025)
Negative bi- is the primary indicator of caritivity in Romani and has been invariably recognized as belonging to the pre-European component of the language. Most lexicographic sources and related studies trace it back to OIA वि vi- ‘un-’, but also acknowledge that an Iranian origin is plausible. In Romani, bi- can function as a preposition, non-verbal privative prefix, conjunction, and verbal prefix. This paper argues that these various constructions can be ascribed to different stages in the development of the language and to different contact scenarios. The limited set of verbs containing a reflex of OIA preverbal वि- vi- and the prototypical circumpositional bi…qo template correspond to an early proto-Romani stage (perhaps late MIA or apabhraṃśa), most certainly prior to the departure from the Indian subcontinent. Strongly adjectival compounds (prefixal bi…qo, bi- + adjectives, bi- + adjectival participles) are more likely to have arisen in a post-Indian context, as a result of contact with Persian or other Iranian languages. Finally, the use of bi as a conjunction with subjunctive verbs must be the result of a later, localized convergence within the Balkan Sprachbund. Drawing on the existing literature and the analysis of various Romani texts, the paper also attempts to disambiguate the morphological status of bi- in genitive nominal formations. The lexical-semantic approach proposed by Lieber (2004) and the picture of overlapping and competing negative prefixes in IE languages outlined by Wackernagel (2009) help explain the functional flexibility and diversity of this lone productive negative prefix as the result of subsequent semantic and functional reconfigurations in various contact scenarios.
Keywords: Romani; bi-; negative; privative; caritive